Purwarupa Pengiriman Informasi Ketinggian Air Sungai Melalui Short Message Service(SMS) Berbasis Arduino Uno - fivtatianti hendajani; Aditya Pranata; Ire Puspa Wardhani; Susi Widayati (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
The development of life and technology at this time is felt to be faster and demands changes in various sectors. Rapid technological advances allow for various businesses to provide convenience and comfort for humans. One of them is through the development of a river water level detection system design. Checking the river water level is usually carried out by monitoring officers. This can be dangerous for officers because the arrival of water is unpredictable. Then the information will be forwarded to the monitoring post and then if needed, residents will ask for news on river water levels by telephone. Information can be felt too late if what happened was a flood of shipments. Residents did not have time to be able to save their lives and property. The river water level information delivery system using Short Massege Service (SMS) can be the solution. Detecting river water levels using a water level which is then processed using Arduino will produce a siren sound and turn on an indicator that indicates the water exceeds the predetermined limit, this can cause flooding. The system will send a short message to authorized residents in the Watershed (DAS) so that they can convey this information to residents immediately. The result of the research is a prototype that has been through trials and the results are in accordance with the research objectives, namely water level information can be sent immediately.